A Critical Study of al-Baidhāwī’s Exegetical Sources: Surah al-Baqarah: 30–32 - Khobir, Abdul; Nasution, Azhar (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2026)
Tafsir al-Bayḍāwī is widely regarded by scholars as one of the most significant forms of ahammu al-tafsīr bi al-ra’y (the most prominent interpretation based on rational inquiry). This assertion appears to contrast with al-Bayḍāwī’s own acknowledgment in the preface of his work, where he mentions referencing various authoritative sources from the ṣaḥābah (Companions) and al-ṣāliḥūn (the righteous predecessors). Against this backdrop, this study aims to critically examine the interpretative sources employed by al-Bayḍāwī in his commentary on QS. al-Baqarah: 30–32. The focus of the study is directed toward several key questions: What types of interpretative sources does al-Bayḍāwī utilize? How stark is the compositional contrast between āthār (traditions) and ra’y (reason) in Tafsir al-Bayḍāwī? Furthermore, how accurate is the application of these interpretative sources? The methodology employed in this study is the critique of interpretative sources (naqd manābi‘ al-tafsīr), referencing the approach proposed by ‘Abd al-Salām bin Ṣāliḥ bin Sulaimān in his work, Naqd al-Ṣaḥābah wa al-Tābi‘īn li al-Tafsīr. The findings indicate that al-Bayḍāwī utilizes a diverse range of interpretative sources, with a predominance of linguistic approaches (tafsīr lughawī). More specifically, it was found that in the interpretation of QS. al-Baqarah: 30–32, al-Bayḍāwī employs nine expressions derived from āthār and nine others from ra’y. These findings confirm that the designation of Tafsir al-Bayḍāwī as ahammu al-tafsīr bi al-ra’y is not merely an assumption but is academically demonstrable. Although some references are considered less ṣaḥīḥ (authentic) or less relevant when evaluated against the riwāyah (tradition-based) approach practiced by the Prophet and the ṣaḥābah, al-Bayḍāwī generally demonstrates a proportional integration between āthār and ra’y in his exegetical construction. Tafsir al-Bayḍāwī secara luas dinilai oleh para ulama sebagai salah satu bentuk ahammu al-tafsīr bi al-ra’y (tafsir ra’yi yang paling penting). Pernyataan ini tampak kontras dengan pengakuan al-Bayḍāwī sendiri di awal karyanya, di mana ia menyebutkan telah merujuk pada berbagai sumber otoritatif dari kalangan para ṣaḥābah dan al-ṣāliḥūn. Berdasarkan latar inilah, Penelitian ini bertujuan untuk mengkaji secara kritis sumber-sumber penafsiran yang digunakan al-Baidhāwī dalam menafsirkan QS. al-Baqarah: 30–32. Fokus kajian diarahkan pada Bagaimana jenis sumber Penafsiran yang digunakan Al-Baidhawi?, Seberapa kontras komposisi antara atsar dan raʾy dalam tafsir Al-baidhawy?, serta bagaimana ketepatan penggunaan sumber-sumber tafsir ini?. Metodologi yang digunakan dalam studi ini adalah kritik sumber tafsir (naqd manābi‘ al-tafsīr), dengan merujuk pada pendekatan yang ditawarkan oleh ‘Abd al-Salām bin Ṣāliḥ bin Sulaimān dalam karyanya Naqd al-Ṣaḥābah wa al-Tābi‘īn li al-Tafsīr. Hasil kajian menunjukkan bahwa al-Bayḍāwī memanfaatkan ragam sumber tafsir, dengan dominasi pendekatan kebahasaan (tafsīr lughawī). Secara lebih spesifik, ditemukan bahwa dalam penafsiran terhadap QS. al-Baqarah: 30–32, al-Bayḍāwī menggunakan sembilan ungkapan yang bersumber dari āṯār (riwayat) dan sembilan lainnya dari ra’y (nalar independen). Temuan ini mengonfirmasi bahwa penyematan gelar ahammu al-tafsīr bi al-ra’y pada Tafsir al-Bayḍāwī bukanlah asumsi belaka, melainkan dapat dibuktikan secara akademik. Meski terdapat sebagian rujukan yang dinilai kurang ṣaḥīḥ atau kurang relevan apabila dikembalikan pada pendekatan tafsir riwāyah sebagaimana praktik Nabi dan para ṣaḥābah, namun secara umum al-Bayḍāwī menunjukkan integrasi yang proporsional antara āṯār dan ra’y dalam konstruksi tafsirnya.